Analisis Cost Overrun (Studi Kasus : Proyek Paper Machine 3 Kab. Pelalawan) - Sahrul Setia; Rian Tri Komara Iriana (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
The implementation of contraction Project is often delay schedule and there has cost overrun. This paper machine project has a set time and cost limit. When the time and the cost have been exhausted but there hasn’t finished the jobs. Therefore, the cost overrun analysis and factor causing are needed to analysis. The analysis used the conceptual method of the result value and interview, which supported by primary and secondary data. Primary data gotten by interview and documentation. Meanwhile, secondary data gotten by written materials as project data. The research result on august showed that the value of variance schedule (SV) is late -0.70%, the variance cost (CV) is reach -0,32%, the variance budged (BV) is 3,19%, schedule Performed Index (SPI) is late 0,96 and cost performed index (CPI) 0,83.The calculation of Estimated At Complication (EAC) is Rp. 59.511.620.988. The cost overrun presentation to the end of the project is 3.5% or Rp. 2.287.285.802 to the contract value. The caused cost overrun are improper cost estimates, incomplete information project, difficulty implementation schedule, the changes of implementation project and weather factor.Keywords: Cost overrun, schedule variants.